Factors associated with serum ferritin among severe dengue patients at a tertiary hospital in Malaysia - Chellappah Thambiah, Subashini; Osman, Malina; Lai, Yin Ye; Zahari Sham, Siti Yazmin; Samsudin, Intan Nureslyna; Rusman, Zety Wizana; Che Rahim, Nur Shafini (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2024)
Introduction: Severe dengue, which poses significant risks of both mortality and morbidity, lacks any specific an- tiviral therapy, underscoring the urgency for predictive biomarkers. Hyperferritinaemia observed in severe cases is thought to stem from excessive activation of monocytes and macrophages. This study aimed to determine factors associated with hyperferritinaemia in hospitalised patient with severe dengue. Materials and methods: A retrospective cross-sectional study was done among patients who were admitted to Hospital Kuala Lumpur with severe dengue in 2017 and 2018. Electronic patient demographic and laboratory data were recorded and analysed. Results:Hyperferritinaemia was observed in 69.2 % of the study population. Gender was significantly associated with ferritin status in severe dengue with significantly higher median ferritin levels in males compared to females. Thrombocytopaenia, raised aspartate transaminase (AST), alanine transaminase (ALT) and haematocrit (HCT) were significantly associated with hyperferritinaemia. Stepwise multilinear regression analysis found that only AST and HCT remained significantly associated with serum ferritin levels, explaining 59.5% of the variance (R² = 0.595) in severe dengue patients. An increase of 1 U/L in AST is associated with a 9.54 µg/L increase in serum ferritin (95% CI: 8.03-11.04), while an increase of 1% in HCT corresponds to a 212.52 µg/L increase in serum ferritin (95% CI: 72.42-352.61). Conclusion: This pilot study found a lower prevalence of hyperferritinaemia compared to previous Asian studies. AST and HCT were independent predictors of serum ferritin in severe dengue patients, highlighting its importance as a biomarker for assessing dengue severity.